2015
DOI: 10.1088/0957-0233/26/11/115604
|View full text |Cite
|
Sign up to set email alerts
|

Determining the propagation angle for non-vertical surface-breaking cracks and its effect on crack sizing using an ACFM sensor

Abstract: Alternating current field measurement (ACFM) probes are used to detect and size cracks in a range of engineering components. Crack sizing for this, and other electromagnetic (EM) based NDT systems, relies on relating the signal obtained to the actual crack length. For cracks that do not propagate vertically, such as rolling contact fatigue cracks in rails, predicting the crack depth, which determines the rail depth to be removed by grinding, requires an assumed propagation angle into the material as no method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
(45 reference statements)
0
17
0
Order By: Relevance
“….5 mm is used in this model. Shen, et al [52] showed that, for RCF cracks propagating into a rail at a range of angles from 30-90 , the ACFM signal response to changing crack vertical angle is insignificant. Hence, the °s ignal can be directly used to determine the crack pocket length.…”
Section: Modelled Crack Parametersmentioning
confidence: 99%
“….5 mm is used in this model. Shen, et al [52] showed that, for RCF cracks propagating into a rail at a range of angles from 30-90 , the ACFM signal response to changing crack vertical angle is insignificant. Hence, the °s ignal can be directly used to determine the crack pocket length.…”
Section: Modelled Crack Parametersmentioning
confidence: 99%
“…As the first step, how to find a tiny crack in a weld is critical work in the ACFM field. The probability of detection (POD) using the ACFM technique decreases drastically for tiny cracks whose lengths are less than 10 mm [16]. Smith et al applied the ACFM technique to inspect the welds in stainless steel nuclear storage tanks [17].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al presented the two-step interpolation algorithm for the measurement of long and short cracks in the pipe string using the uniform alternating current field [19]. Leng et al proposed the combined metal magnetic memory (MMM) and the ACFM The probability of detection (POD) using the ACFM technique decreases drastically for tiny cracks whose lengths are less than 10 mm [16]. Smith et al applied the ACFM technique to inspect the welds in stainless steel nuclear storage tanks [17].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical depth varies depending on the crack vertical angle and crack pocket length, as shown in Figure 1c. It has recently been reported that the Bz trough-peak ratio, derived from a single measurement line across the centre of the crack at 45°, can be used to obtain the crack vertical angle, which can then be used with the determined crack pocket length to give the vertical depth [14]. This provides a guide for railway grinding to remove the RCF cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of ACFM Bx signals to various surface lengths, inner spacings and crack numbers for crack clusters have been reported but only cracks with vertical angles of > 30° were considered [16]. Previous studies [14,22] have shown that shallow vertical angles (< 30°) give different Bx signals compared to those obtained for cracks with vertical angles >30° for single and clustered cracks, leading to under estimation of crack pocket lengths. It is important to be able to characterise crack clusters, as RCF cracks usually present in the form of clusters and with vertical angles less than 30°.…”
Section: Introductionmentioning
confidence: 99%